Sea Pandan Leaf Fiber as an Alternative Material for Upper Limb Orthosis - Mutmainnah, Aisya Fitri; Rachmadita, Alya Febi; Yuliyanti, Annisa Mufid; Utomo, Prasetyo Catur (Journal of Prosthetics Orthotics and Science Technology, 2025)
Background: The use of natural materials as an alternative to reduce the use of chemicals. One of the steps is the utilization of natural fibers from sea pandan leaves as a substitute for fiberglass chemicals in the process of making assistive devices for upper limb deformities. Objective: The objective of this scientific work is to utilize synthetic fiber alternatives used in the production of upper limb orthoses. Method: The data collection method used by the researcher is by tracing primary data: observing the composite results of sea pandan leaf fibers. Results: The experimental results show that fibers from sea pandan leaves soaked in a solution of 6 grams of NaOH and 3000 ml of water for one hour, then dried for 24 hours, can be used as a reinforcing material. By using 342.72 ml of resin and 6.8 ml of catalyst, these sea pandan fibers can optimally absorb the resin, thereby forming a sturdy composite structure through the thermal hardening process. The final product produced is a Wrist-Hand Orthosis (WHO) designed to address cases of Carpal Tunnel Syndrome (CTS). This orthosis demonstrates good shape and rigidity, although it is not as strong as fiberglass. The main advantage of sea pandanus fiber is its environmentally friendly properties and natural origin. Conclusion: Sea pandan leaf fibers are a promising alternative to replace fiberglass in WHO production in CTS cases. The process of soaking the fibers in NaOH solution has been proven to enhance resin absorption and strengthen the material's strength. The research results show that this natural fiber has the ability to provide good strength and stiffness, while remaining an environmentally friendly option and supporting the sustainable use of local natural resources.